Problematika Kepentingan Nasional Sebagai Alasan Pengakhiran Perjanjian Internasional - Mardiyanto, Ibnu (Magister Ilmu Hukum - Universitas Hang Tuah, 2022)
Evidence of the existence of the enforceability of international law is the reciprocal relationship between members of the international community, one of which can be implemented through international agreements. State relations in international agreements make th e no r m s born of them binding on the parties and make these norms guidelines for third party co untr ie s in entering into international contracts by the provisions applicable in the global legal s y s tem . The research method used in this article is normative legal research with the app ro ach us e d to analyze the problems in this research, including the conceptual approach and th e co m pa r ative approach. This study concludes that Indonesia's engagement as a third party in the 1969 Vienna Convention through the ratification process makes it obligatory to transform the provisions of international treaties in the Convention into its national legalsystem. One o f th e efforts to harmonize the Law on International Treaties with the 1969 Vienna Conventio n is to eliminate reasons of national interest as the reason for terminating participation in international agreements because these reasons are not regulated in the legal norms of international treaties.